The introduction of a minimum wage in Germany and the effects on physical activity participation - Sören Dallmeyer; Christoph Breuer (International Journal of Health Economics and Management, 2024)
Abstract The relationship between income and physical activity has been extensively studied. This paper utilizes the introduction of the minimum wage in Germany in 2015 as a quasi-experiment to determine the causal effect of minimum wages on the frequency of physical activity participation. Employing survey data from the German Socio-Economic Panel between 2013 and 2017, regression-adjusted difference-in-difference models combined with matching techniques are estimated. Our findings reveal a notable negative effect immediately after the minimum wage implementation on physical activity frequency. Given that the introduction of the minimum wage did not increase monthly gross income but reduced working hours, it appears that affected individuals exhibit preferences and engage in utility maximization that do not emphasize healthy behaviors. This effect is particularly pronounced among older females in white-collar occupations.
Additional information: I12;I14;I18
Keywords: 330; Physical activity; Minimum wage; GSOEP; Public health